Role of university reputation towards student choice to private universities - Aesya A., Shamsudin M.F., Nurana N.,; Abdel Nabi, Milad (Opción, 2019)
The aim of this research was to evaluate the factors that affected student enrolment at a private university in Malaysia. This study was conducted using the quantitative method. Measurement for each variable was using the Likert scale. The finding of data was analysed by using SPSS software version 20. The finding shows that there is a significant relationship between location and student decision making. In conclusion, the leading most influential criteria that made up this factor is the institution reputation for quality as it has the highest means score.